Aplicación de modelo de gestión por procesos orientado a la mejora académica y administrativa en la Unidad Educativa “Cristo del Consuelo” - Flores Soria, Andrea Paola (2011)
This work took place in the Cristo del Consuelo Education Unit located in the neighborhood Firsts Culture of Quito, in the citadel Ibarra Chillogallo Parish, Canton Quito, Pichincha province, the theme was set against the needs that had the instituion, the proposal is to implement a management model for processes to help improve the development of the activities of the same, as the institution has a social assistance to the poor people trying to give quality education .